Method for producing dense sintered body of β-type tricalcium phosphate for use as biomaterial
Patent Information
- Application Number
- JP2023137620
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0011】 本発明によれば、従来よりも焼結率が高く、焼結率97%以上の焼結体で、かつ、かさ密度が3.0g/cm3以上の焼結体からなる緻密質のβ型リン酸三カルシウムで構成された生体材料用β型リン酸三カルシウムの緻密質焼結体製造方法を提供することができる。
Smart Images

Figure 2025031407000003 
Figure 2025031407000004 
Figure 2025031407000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial. [Background technology]
[0002] β-tricalcium phosphate (hereinafter referred to as "β-Ca 3 (PO 4 ) 2 Porous β-TCP is also sometimes written as "β-TCP". It has high biocompatibility and bioabsorption, and has the property of replacing autologous bone, so it is used clinically as a bone filler used to repair bone defects. Among them, porous β-TCP has an appropriate pore size and porosity, and bone tissue can grow inside the porous body, so it is used as a scaffolding material to promote the repair of bone tissue itself. On the other hand, dense β-TCP is used as a spacer for bone defects and the iliac bone, etc., where relatively high mechanical strength is required. The manufacturing methods of porous β-TCP and dense β-TCP are significantly different due to the difference in the microstructure of the sintered body.
[0003] A typical method for producing porous β-TCP is to add a nonionic surfactant to raw powder of β-TCP to form a mixture, foam and dry the mixture by physical stirring, and sinter the resulting dried product at a sintering temperature of 1000° C. to 1100° C. Another method for producing porous β-TCP is to add a template material (pore-forming agent) such as a polymer or carbon to raw powder of β-TCP to form a molded product, heat the molded product at a high temperature, and remove the template material by burning to obtain porous β-TCP having pores.
[0004] On the other hand, as a method for producing dense β-TCP, a method is generally mentioned in which a raw powder of calcium salts and a raw powder of phosphates are mixed at a Ca / P molar ratio of 1.50, calcined at 700°C to 1000°C, the calcined raw material is molded by primary molding and cold isostatic pressing (CIP), and the obtained molded body is sintered at 1100°C to 1150°C for 5 to 48 hours by a controlled sintering program. Also, as a method for producing dense β-TCP, a method is mentioned in which a raw powder of calcium salts and a raw powder of phosphates are mixed at a Ca / P molar ratio of 1.50, a precursor obtained by using a mechanochemical method, a hydrothermal synthesis method, an aqueous solution method, or the like is calcined at 700°C to 1000°C, the calcined raw material is molded by primary molding and CIP, and the obtained molded body is sintered at 1100°C to 1150°C for 5 to 48 hours by a controlled sintering program. Generally, the sintering temperature of a dense body is higher than that of a porous body.
[0005] Furthermore, methods for producing dense β-TCP are known, such as those described in Non-Patent Documents 1 and 2. Both of these methods aim to densify the material by adding an oxide-based sintering aid and sintering at high temperatures of 1150°C or higher.
[0006] Furthermore, as a method for producing dense β-TCP, the method described in Non-Patent Document 3 is known. In the reactive sintering method, β-TCP is unlikely to become a single phase, and the bulk density of the obtained sintered body is 1.7 g / cm 3 ~2.5g / cm 3 It was. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] AKAO. M. etc. Yogyo-Kyokai-Shi, 92
[11] , 672-674 1984 [Non-Patent Document 2] Toriyama, Motohiro et al., Journal of the Ceramic Society of Japan 96[8]. 837-841 (1988) [Non-Patent Document 3] Yoshida.K, etc., Journal of the European Ceramic Society 27.3215-3220(2007) Summary of the Invention [Problem to be solved by the invention]
[0008] Conventional methods for manufacturing dense β-TCP had issues such as: (1) insufficient sinterability, (2) insufficient mechanical strength, (3) impurities in the chemical composition, and (4) the physical properties of dense β-TCP are unclear. (1) Lack of sinterability: In the solid-phase method using a calcined product of general calcium salts and phosphates, when sintering at 1100°C to 1150°C, a sintered body with a porosity of only 5% to 15% is obtained, making it difficult to manufacture a high-density sintered body. In order to improve the sinterability of the sintered body, it is necessary to fire at a higher temperature than this, which increases energy consumption. However, heating at 1150°C for a long time causes a crystal structure transition. In other words, a crystal structure change from β-TCP to α-tricalcium phosphate (α-TCP) occurs, and the desired dense β-TCP cannot be obtained. (2) Insufficient mechanical strength: Pores present within the sintered body and on the surface of the sintered body lead to a decrease in three-point bending strength and compressive strength, resulting in insufficient mechanical strength. (3) Impurities in the chemical composition: In the production of dense β-TCP, the substitution and solid solution of metal ions as sintering aids is necessary. However, this results in the inclusion of impurities other than calcium and phosphorus, which has an adverse effect on the solubility and other properties of dense β-TCP. (4) The physical properties of dense β-TCP are unclear: Conventional methods for producing dense β-TCP use sintering additives (MgO, SiO 2 It requires high energy consumption under special conditions, such as the addition of β-TCP, high-temperature sintering at 1200℃ to 1300℃, which is above the α-transition temperature, and molding at high pressure (hot press, HIP), and there is no method that is energy-saving and easy to operate experimentally. In addition, there have been no reports of high-purity, high-density β-TCP with accurate physical properties, which limits the uses of dense β-TCP.
[0009] The present invention has been made in view of the above circumstances, and provides a sintered body having a sintering rate of 97% or more, which is higher than that of conventional sintered bodies, and a bulk density of 3.0 g / cm. 3 An object of the present invention is to provide a method for producing a dense sintered β-tricalcium phosphate for use as a biomaterial, which is made of the above-mentioned dense β-tricalcium phosphate sintered body. [Means for solving the problem]
[0010] The present invention has the following aspects. [1] A raw material blending step of blending calcium salts and phosphate salts to obtain a mixture having a molar ratio of calcium to phosphorus (Ca / P) of 1.50; a molding step of molding the mixture into a molded body; and a sintering step of sintering the molded body at 1100°C or higher and 1150°C or lower by a reaction sintering method to obtain a sintered body made of β-tricalcium phosphate, A method for producing a dense sintered body of β-tricalcium phosphate for biomaterials, comprising using hydroxyapatite of stoichiometric composition as a raw material in the raw material blending step. [2] The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to [1], wherein the average primary particle size of the mixture is 0.1 μm or more and 800 μm or less. [3] The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to [1] or [2], wherein in the molding step, the mixture is molded into a molded body by a direct molding method and a cold isostatic pressing method. [4] The chemical composition of the mixture is composed of phosphoric acid and calcium forming β-tricalcium phosphate; The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to any one of [1] to [3], wherein in the molding step, the mixture is molded into a molded body without adding a third component which is a sintering aid. [5] In the forming step, the mixture is formed into a molded body without using hot pressing, hot isostatic pressing, or spark plasma sintering; The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to any one of [1] to [4], wherein the sintering step is performed by sintering the molded body without using hot pressing, hot isostatic pressing or spark plasma sintering. [6] A method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial according to any one of [1] to [5], in which hydroxyapatite of a stoichiometric composition obtained by a reactive sintering method is used as a raw material for the dense sintered body of β-tricalcium phosphate for use as a biomaterial. Effect of the Invention
[0011] According to the present invention, a sintered body with a sintering rate of 97% or more, which is higher than that of the conventional sintered body, and a bulk density of 3.0 g / cm3 can be obtained. 3 It is possible to provide a method for producing a dense sintered β-tricalcium phosphate for use as a biomaterial, which is made of the dense β-tricalcium phosphate composed of the above-mentioned sintered body. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a diagram showing the results of X-ray diffraction of the sintered bodies obtained in the examples and comparative examples. [Diagram 2] FIG. 2 is a diagram showing the results of X-ray diffraction of the sintered body obtained in Example 1. [Diagram 3] FIG. 2 is a diagram showing the results of simultaneous differential thermal and thermogravimetry measurements of the sintered body obtained in Example 1. [Figure 4] FIG. 2 is a diagram showing the results of thermomechanical analysis of the sintered body obtained in Example 1. [Diagram 5] 1 is a field emission scanning electron microscope image of the sintered body obtained in Example 1. [Figure 6] 1 is a field emission scanning electron microscope image of the sintered body obtained in Example 1. [Figure 7] FIG. 2 is a diagram showing the results of X-ray diffraction of the sintered body obtained in Comparative Example 1. [Figure 8] FIG. 2 is a diagram showing the results of simultaneous differential thermal and thermogravimetry measurements of the sintered body obtained in Comparative Example 1. [Figure 9]FIG. 2 is a diagram showing the results of thermomechanical analysis of the sintered body obtained in Comparative Example 1. [Figure 10] 1 is a field emission scanning electron microscope image of the sintered body obtained in Comparative Example 1. [Figure 11] 1 is a field emission scanning electron microscope image of the sintered body obtained in Comparative Example 1. [Figure 12] 1 is a field emission scanning electron microscope image of the sintered body obtained in Example 2. [Figure 13] 1 is a field emission scanning electron microscope image of the sintered body obtained in Example 2. [Figure 14] 1 is a field emission scanning electron microscope image of the sintered body obtained in Comparative Example 2. [Figure 15] 1 is a field emission scanning electron microscope image of the sintered body obtained in Comparative Example 2. [Figure 16] 1 is a field emission scanning electron microscope image of the sintered body obtained in Example 3. [Figure 17] 1 is a field emission scanning electron microscope image of the sintered body obtained in Example 3. [Figure 18] 1 is a field emission scanning electron microscope image of the sintered body obtained in Comparative Example 3. [Figure 19] 1 is a field emission scanning electron microscope image of the sintered body obtained in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] An embodiment of the method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial according to the present invention will be described. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.
[0014] [Method of manufacturing dense sintered β-tricalcium phosphate for biomaterials] A method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to one embodiment of the present invention comprises a raw material blending step of mixing calcium salts and phosphates to obtain a mixture with a molar ratio of calcium to phosphorus (Ca / P) of 1.50, a molding step of molding the mixture into a molded body, and a sintering step of sintering the molded body at 1100°C to 1150°C by a reactive sintering method to obtain a sintered body made of β-tricalcium phosphate. In the method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to this embodiment, hydroxyapatite of stoichiometric composition is used as the raw material in the raw material blending step.
[0015] "Raw material blending process" Examples of calcium salts include calcium carbonate (CaCO 3 ), calcium phosphate dihydrate (CaHPO 4 2H 2 O:DCPD), calcium diphosphate (Ca 2 P 2 O 7 ) Hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 HAp), calcium oxide (CaO), calcium hydroxide (Ca(OH) 2 ), calcium nitrate (Ca(NO 3 ) 2 ), calcium chloride (CaCl 2 ), calcium acetate, calcium malate, calcium citrate, and other organic acid calcium salts. Among these, calcium carbonate (CaCO 3 ), calcium hydroxide (Ca(OH) 2 ), calcium phosphate dihydrate (CaHPO 4 2H 2 O), dibasic calcium phosphate (Ca 2 P 2 O 7 :CPP), hydroxyapatite (Ca 10 (PO 4 )6 (OH) 2 :abbreviated as HAp) is preferred. Examples of phosphates include diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 ), ammonium dihydrogen phosphate ((NH 4 )H 2 PO 4 ), triammonium phosphate ((NH 4 ) 3 PO 4 ), calcium hydrogen phosphate (CaHPO 4 : DCPA), dicalcium hydrogen phosphate dihydrate (CaHPO 4 2H 2 O:DCPD), dibasic calcium phosphate (Ca 2 P 2 O 7 :CPP), hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 : HAp), tetracalcium phosphate (Ca 4 O(PO 4 ) 2 Among these, diammonium hydrogen phosphate, DCPD, and HAp are preferred from the viewpoint of simultaneous progress of decomposition reaction and solid-phase diffusion reaction at high temperatures during reaction sintering.
[0016] The average primary particle size of the mixture is preferably 0.1 μm to 800 μm, more preferably 1 μm to 100 μm, and even more preferably 0.5 μm to 10 μm. If the average primary particle size of the mixture is below the lower limit, the particle size distribution becomes broad, and fine particles are fused into large particles by sintering, which may cause abnormal grain growth. On the other hand, if the average primary particle size of the mixture is above the upper limit, the particle distribution of the obtained sintered body becomes large, which has no positive effect on the mechanical strength, etc.
[0017] The particle shape of the mixture is preferably an irregular shape, a spherical shape, etc. Among these, from the viewpoint of increasing the filling property of the molded body, needle-like and fibrous shapes are not preferable, and equiaxial irregular and spherical shapes are preferable. In the manufacturing method of the biomaterial ceramic according to this embodiment, it is preferable that the particle shapes of all calcium salts used are uniform.
[0018] The average primary particle size of the mixture can be measured by a laser diffraction particle size distribution analyzer (MT-3300EX II) manufactured by Microtrack Bell after dispersing the mixture in a 0.2 mass % aqueous solution of sodium hexametaphosphate using an ultrasonic homogenizer.
[0019] In the mixing step, calcium salts and phosphates are mixed so that the molar ratio of calcium to phosphorus (Ca / P) is 1.50. If the ratio of calcium to phosphorus (Ca / P) is not 1.50, calcium diphosphate will be mixed in as an impurity if it is less than 1.50, and apatite will be mixed in as an impurity if it exceeds 1.50.
[0020] Examples of the method for mixing the calcium salts and the phosphates include dry mixing, wet ball mill mixing, and wet bead mill mixing.
[0021] Examples of hydroxyapatite used in this embodiment include compounds having an apatite structure such as hydroxyapatite of a stoichiometric composition, hydroxyapatite of a non-stoichiometric composition in which some of the Ca ions are missing and replaced with protons, and carbonated hydroxyapatite in which some of the phosphate ions are replaced with carbonate ions. Among these, from the viewpoint of accurately performing the compounding for reactive sintering, hydroxyapatite of a stoichiometric composition (Ca 10 (PO 4 ) 6 (OH) 2 ) is preferred. In the manufacturing method of dense sintered β-tricalcium phosphate for biomaterials of this embodiment, hydroxyapatite functions first as a starting material for calcium salts and phosphates, and also as a sintering aid in which decomposition products produced by the decomposition reaction of apatite at high temperatures promote the production of β-tricalcium phosphate at low temperatures with surrounding calcium phosphate salts, etc., and further as a sintering aid in promoting the expulsion of pores generated inside by the discharge to the outside of water molecules generated by the decomposition reaction of apatite. These functions contribute to the densification of β-tricalcium phosphate sintered bodies at low temperatures.
[0022] As a method for mixing the above mixture with hydroxyapatite, for example, a ball mill method using ethanol as a solvent can be mentioned.
[0023] "Molding process" In the molding step, the mixture to which the hydroxyapatite has been added is molded into a molded body. In the molding step, it is preferable to mold the mixture into a molded body by a direct molding method and a cold isostatic pressing method, that is, first, the mixture to which hydroxyapatite has been added is molded into a predetermined shape by the direct molding method to obtain a precursor of the molded body, and then the precursor is isostatically pressed by the cold isostatic pressing method to obtain the molded body.
[0024] The pressure when the precursor is pressed by the cold isostatic pressing method is preferably 100 MPa to 250 MPa, more preferably 150 MPa to 200 MPa. When the pressure is equal to or higher than the lower limit, the molding density of the molded body is high, and a high-density β-tricalcium phosphate sintered body is obtained. When the pressure is equal to or lower than the upper limit, no intragranular fracture of the molded particles occurs, and a high-density β-tricalcium phosphate sintered body is obtained.
[0025] The chemical composition of the mixture is composed of phosphoric acid and calcium, which form β-tricalcium phosphate, and it is preferable to mold the mixture into a molded body without adding a third component, which is a sintering aid, in the molding step.
[0026] In the forming step, the mixture is preferably formed into a compact without using hot pressing, hot isostatic pressing or spark plasma sintering.
[0027] "Sintering process" In the sintering step, the molded body obtained in the molding step is sintered at 1100° C. or more and 1150° C. or less by a reactive sintering method to obtain a sintered body made of β-tricalcium phosphate. If the temperature for sintering the molded body is less than the lower limit, the sintered density of the resulting sintered body will not be high, and a high-density β-tricalcium phosphate sintered body will not be obtained.If the temperature for sintering the molded body is more than the upper limit, crystal transition will occur and the molded body will change to α-tricalcium phosphate.
[0028] In the firing step, it is preferable to sinter the molded body without using hot pressing, hot isostatic pressing or spark plasma sintering.
[0029] According to the method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to the present embodiment, the sintering rate is 97% or more and the bulk density is 3.0 g / cm 3 A dense sintered body of β-tricalcium phosphate for biomaterials made of dense β-tricalcium phosphate consisting of the above sintered body is obtained. The dense sintered body of β-tricalcium phosphate for biomaterials obtained has an open porosity of 1% or less, and the other pores are closed porosity.
[0030] In the method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to the present embodiment, a mixture containing calcium salts and phosphates having a predetermined range of average primary particle size and hydroxyapatite of a stoichiometric composition is molded into a molded body by direct molding and cold isostatic pressing, and the molded body is sintered by reactive sintering at a temperature lower than the alpha transition temperature, 1100°C to 1150°C. In the method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to the present embodiment, it is considered that by using hydroxyapatite, the sintering phenomenon starting at 800°C and the decomposition reaction of hydroxyapatite and calcium compounds and / or phosphate compounds therearound combine to promote the sintering reaction, and sintering is promoted by the effect of water molecules due to the dehydration of hydroxyapatite by heating at high temperatures.
[0031] According to the method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial according to this embodiment, the sintering method for molded bodies, which has conventionally been performed using a general solid-phase method, is changed to a reactive sintering method. This enables the sintering temperature and sintering time to be optimized, making it possible to sinter at a lower temperature than before, thereby reducing energy consumption.
[0032] According to the method for producing dense sintered β-tricalcium phosphate for biomaterials according to the present embodiment, densification is achieved by reactive sintering, without substitution solid solution as in the past, and therefore the amount of impurities contained in the resulting biomaterial ceramics can be reduced. For example, by using high-purity calcium salt and phosphate raw materials that become only calcium salts and / or phosphates when heated at high temperatures, the inclusion of impurities other than calcium and phosphates in the reactive sintering method can be minimized. This makes it possible to almost completely suppress the effect on the solubility of the resulting β-tricalcium phosphate.
[0033] According to the method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial according to this embodiment, a reactive sintering method is used to sinter the molded body, and therefore the molded body is fired without being pre-fired. This omits the pre-firing step according to the conventional solid phase method, thereby simplifying the production process.
[0034] According to the method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to the present embodiment, by using reactive sintering, the porosity of the dense β-tricalcium phosphate can be reduced to 3% or less, resulting in a sintering rate of 97% or more and a bulk density of 3.0 g / cm. 3 It is possible to improve the mechanical strength of biomaterial ceramics made of the above-mentioned high-density β-tricalcium phosphate. In addition, by optimizing the particle shape and average primary particle size of the raw material powder used in reaction sintering, it is possible to obtain a sintered body with a uniform particle size distribution. Furthermore, by using reaction sintering, the sintering temperature can be lowered, and by matching the shrinkage of the molded body due to sintering with the heating rate, it is possible to appropriately expel the internal pores to the outside, resulting in a dense sintered body. EXAMPLES
[0035] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0036] Table 1 shows the amounts of calcium salts and phosphates used in the examples of the present invention and the comparative examples. Blends 1, 3, and 5 are comparative examples, and blends 2, 4, and 6 are examples. In all blends, the Ca / P molar ratio is 1.50.
[0037] [Table 1]
[0038] The physical properties of the sintered bodies obtained in the examples and comparative examples related to the present invention are shown in Table 2. Note that these results were obtained by the Archimedes method, which is a method for evaluating the physical properties of ceramics. The results of the comparative examples, formulations 1, 3, and 5, were 3.0 g / cm 3 The results of the following low density β-type tricalcium phosphate are 3.0 g / cm 3 It was found to be a high-density beta-tricalcium phosphate exceeding 1000 nm.
[0039] [Table 2]
[0040] FIG. 1 shows the results of X-ray diffraction of the sintered bodies obtained in the examples and comparative examples of the present invention. From Figure 1, only the comparative example of Blend 1 showed a slight X-ray diffraction pattern of HAp, indicating that it was a mixture of β-tricalcium phosphate and HAp. However, all other blends showed only the diffraction lines of β-tricalcium phosphate, indicating that they were pure β-tricalcium phosphate of a single phase. The Mini Flex 600 manufactured by Rigaku was used as the X-ray diffraction device.
[0041] [Example 1 (Formulation 2)] "Preparation of sintered bodies" Calcium phosphate dihydrate (CaHPO 4 2H 2 O) 10.175g and hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 14.825 g of the above was placed in a plastic bottle-shaped container, dispersed in ethanol using a ball mill with alumina balls having a diameter of 4 mm, and stirred and mixed at room temperature for 24 hours. Next, the ethanol contained in the ethanol solution was removed using a rotary evaporator to obtain a mixed powder containing calcium phosphate dihydrate and hydroxyapatite. Next, 84% by mass of the obtained powder, 8% by mass of an aqueous polyvinyl alcohol solution having a concentration of 2% by mass, and 8% by mass of pure water were mixed in a plastic container to prepare a plastic powder aggregate. The resulting plastic powder aggregate was then granulated by passing it through a nylon sieve to obtain granules having a particle size of 200 μm or less. Next, 95% by mass of the obtained granules and 5% by mass of kerosene as a lubricant were mixed in a plastic container to prepare a material for compacts. Next, the obtained material for a molded body was filled into a metal mold and uniaxially press-molded at room temperature and a pressure of 100 MPa for 1 minute to obtain a precursor of a molded body. Next, the plastic vacuum packing bag containing the precursor of the molded body was vacuum sealed using a tabletop vacuum packing machine to obtain a sample for cold isostatic pressing. The vacuum-sealed sample was then subjected to water pressure molding at room temperature and a pressure of 200 MPa for 10 minutes by cold isostatic pressing to obtain a green body. Next, the green body was heated to 800°C at a heating rate of 3°C / min accompanied by a debinding process at a low temperature, and then heated to 1120°C at a heating rate of 1°C / min, and sintered at 1120°C for 48 hours to obtain a sintered body.
[0042] "evaluation" (1) X-ray diffraction The obtained sintered body was subjected to X-ray diffraction (XRD). The X-ray diffraction device used was a Rigaku Mini Flex 600. The results of the X-ray diffraction are shown in Figure 2. For comparison, X-ray diffraction (XRD) was performed on the material for the compact before sintering (DCPD+HAp shown in Figure 2), the sintered compacts sintered at 300°C, the sintered compacts sintered at 600°C, and the sintered compacts sintered at 900°C. From the results shown in Figure 2, it was found that the raw powder was a mixture of DCPD and HAp, and when heated, the reaction proceeded through the thermal dehydration of DCPD and the dehydration and decomposition of HAp, ultimately resulting in β-tricalcium phosphate.
[0043] (2) Simultaneous differential thermal and thermogravimetric (TG-DTA) measurement To investigate the change in the thermal stability of the obtained sintered body, TG-DTA measurement was performed. The TG-DTA measurement was performed using a Rigaku thermogravimetric differential thermal analyzer TG-DTA8122 at a heating rate of 10°C / min, in the measurement temperature range of room temperature to 1200°C, in air. The results are shown in Figure 3. From the results shown in FIG. 3, it was found that the sintering reaction proceeded due to the thermal dehydration of DCPD by heating at 120°C to 200°C and 350°C to 550°C, and due to the dehydration and decomposition of HAp by heating at 700°C to 800°C.
[0044] (3) Thermomechanical analysis (TMA) TMA was performed to investigate the deformation of the obtained sintered body with respect to temperature. TMA was performed using a Rigaku thermomechanical analyzer TDL8 II at a heating rate of 10°C / min, in the measurement temperature range of room temperature to 1200°C, and in air. The results are shown in Figure 4. The results shown in Figure 4 indicate that when hydroxyapatite was mixed with various raw materials, the samples began to shrink as sintering progressed from 800°C.
[0045] (4) Field emission scanning electron microscope (FE-SEM) observation The obtained sintered body was observed with a field emission scanning electron microscope. A JEOL field emission scanning electron microscope, JSM-IT800, was used as the field emission scanning electron microscope. In order to prepare the specimen, the surface of the specimen was mirror polished and then heated at 1020°C for 3 hours for thermal etching. Gold was then evaporated (vacuum device: MSP-1S) and the specimen was observed. The results are shown in Figures 5 and 6. Figure 5 shows a field emission scanning electron microscope image at 1000x magnification, and Figure 6 shows a field emission scanning electron microscope image at 5000x magnification. From the results shown in FIG. 5 and FIG. 6, it was found that the obtained sintered body was a dense material with particles of 2 μm to 5 μm.
[0046] (5) Evaluation of physical properties of sintered bodies using Archimedes method The physical properties of the sintered body were evaluated by the Archimedes method. Bulk density: 3.02 g / cm 3 The open porosity was 0.1%, the closed porosity was 1.4%, and the sintering rate was 98.5%, which revealed that it was a highly dense sintered body. The sintering rate was calculated by (bulk density) ÷ (theoretical density) × 100.
[0047] [Comparative example 1 (formulation 1)] "Preparation of sintered bodies" Calcium phosphate dihydrate (CaHPO 4 2H 2 O) 18.275 g and calcium carbonate (CaCO 3A sintered body of Comparative Example 1 was obtained in the same manner as in Example 1 using 6.725 g of the above powder.
[0048] "evaluation" (1) X-ray diffraction X-ray diffraction (XRD) of the obtained sintered body was carried out in the same manner as in Example 1. The results of X-ray diffraction are shown in FIG. 7. For comparison, the material for the compact before sintering (DCPD + calcium carbonate (CaCO 3 ), sintered bodies sintered at 300°C, sintered bodies sintered at 600°C, and sintered bodies sintered at 900°C were subjected to X-ray diffraction (XRD). From the results shown in Figure 7, the raw powder is a mixture of DCPD dehydration and calcium carbonate (CaCO 3 ) and ultimately to form β-tricalcium phosphate.
[0049] (2) Simultaneous differential thermal and thermogravimetric (TG-DTA) measurement The TG-DTA measurement of the obtained sintered body was carried out in the same manner as in Example 1. The results are shown in FIG. From the results shown in FIG. 8, it was found that heating at 120°C to 200°C and 350°C to 550°C promoted the thermal dehydration of DCPD, and heating at 600°C promoted the decomposition reaction of calcium carbonate (decarbonation), which promoted the sintering reaction of the heated product.
[0050] (3) Thermomechanical analysis (TMA) measurement The resulting sintered body was subjected to TMA measurement in the same manner as in Example 1. The results are shown in FIG. From the results shown in Figure 9, it was found that for samples in which hydroxyapatite was not mixed into the various raw materials, shrinkage occurred as sintering progressed from 900°C.
[0051] (4) Field emission scanning electron microscope (FE-SEM) observation The obtained sintered body was observed under a field emission scanning electron microscope in the same manner as in Example 1. The results are shown in Figures 10 and 11. Figure 10 shows a field emission scanning electron microscope image at 1000x magnification, and Figure 11 shows a field emission scanning electron microscope image at 5000x magnification. From the results shown in Figs. 10 and 11, it was found that the obtained sintered body was porous with pores present in the microstructure.
[0052] (5) Evaluation of physical properties of sintered bodies using Archimedes method The physical properties of the sintered body were evaluated by the Archimedes method. Bulk density: 2.17 g / cm 3 The open porosity was 28.3%, the closed porosity was 0.8%, and the sintering rate was 70.8%, revealing that the bulk density was low and the sintering rate was not high.
[0053] [Example 2 (Formulation 4)] "Preparation of sintered bodies" Instead of calcium phosphate dihydrate shown in Example 1, β-dibasic calcium phosphate (Ca 2 P 2 O 7 ) 8.400g, hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 The other production conditions were the same as in Example 1, and a sintered body of Example 2 was obtained.
[0054] "evaluation" (1) Field emission scanning electron microscope (FE-SEM) observation The obtained sintered body was observed with a field emission scanning electron microscope in the same manner as in Example 1. The results are shown in Figures 12 and 13. Figure 12 shows a field emission scanning electron microscope image at 1000 magnifications, and Figure 13 shows a field emission scanning electron microscope image at 5000 magnifications. From the results shown in Figs. 12 and 13, it was found that the obtained sintered body was a dense material with particles of 1 to 5 µm.
[0055] (2) Evaluation of physical properties of sintered bodies using Archimedes method The physical properties of the sintered body were evaluated by the Archimedes method. Bulk density: 3.02 g / cm 3 The open porosity was 0.2%, the closed porosity was 1.5%, and the sintering rate was 98.2%, making it clear that this was a highly dense sintered body.
[0056] [Comparative example 2 (formulation 3)] "Preparation of sintered bodies" The β-dibasic calcium phosphate (Ca 2 P 2 O 7 21.475 g of hydroxyapatite was mixed with 4.525 g of calcium oxide (CaO) as a calcium salt in place of hydroxyapatite. The other production conditions were the same as in Example 2, and a sintered body of Comparative Example 2 was obtained.
[0057] "evaluation" (1) Field emission scanning electron microscope (FE-SEM) observation The obtained sintered body was observed with a field emission scanning electron microscope in the same manner as in Example 1. The results are shown in Figures 14 and 15. Figure 14 shows a field emission scanning electron microscope image at 1000 magnifications, and Figure 15 shows a field emission scanning electron microscope image at 5000 magnifications. From the results shown in Figs. 14 and 15, it was found that the obtained sintered body was porous with pores present in the microstructure.
[0058] (2) Evaluation of physical properties of sintered bodies using Archimedes method The physical properties of the sintered body were evaluated by the Archimedes method. Bulk density: 2.27 g / cm 3 The open porosity was 25.3%, the closed porosity was 0.8%, and the sintering rate was 73.9%, revealing that the bulk density was low and the sintering rate was not high either.
[0059] [Example 3 (Composition 6)] "Preparation of sintered bodies" Instead of calcium phosphate dihydrate shown in Example 1, diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 ) 2.025g was used to prepare a hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 The other production conditions were the same as in Example 1, and a sintered body of Example 3 was obtained.
[0060] "evaluation" (1) Field emission scanning electron microscope (FE-SEM) observation The obtained sintered body was observed under a field emission scanning electron microscope in the same manner as in Example 1. The results are shown in Figures 16 and 17. Figure 16 shows a field emission scanning electron microscope image at 1000x magnification, and Figure 17 shows a field emission scanning electron microscope image at 5000x magnification. From the results shown in Figs. 16 and 17, it was found that the obtained sintered body was a dense material with particles of 10 to 30 µm.
[0061] (2) Evaluation of physical properties of sintered bodies using Archimedes method The physical properties of the sintered body were evaluated by the Archimedes method. Bulk density: 3.03 g / cm 3 The open porosity was 0.1%, the closed porosity was 1.0%, and the sintering rate was 98.8%, revealing that it was a highly dense sintered body.
[0062] [Comparative example 3 (formulation 5)] "Preparation of sintered bodies" Calcium phosphate dihydrate (CaHPO 4 2H 2 O) 18.075 g, and calcium hydroxide (Ca(OH) 2 The other production conditions were the same as in Example 1, and a sintered body of Comparative Example 3 was obtained.
[0063] "evaluation" (1) Field emission scanning electron microscope (FE-SEM) observation The obtained sintered body was observed with a field emission scanning electron microscope in the same manner as in Example 1. The results are shown in Figures 18 and 19. Figure 18 shows a field emission scanning electron microscope image at 1000 magnifications, and Figure 19 shows a field emission scanning electron microscope image at 5000 magnifications. The results shown in Figs. 18 and 19 indicate that the obtained sintered body was porous.
[0064] (2) Evaluation of physical properties of sintered bodies using Archimedes method The physical properties of the sintered body were evaluated by the Archimedes method. Bulk density: 2.53 g / cm 3 The open porosity was 16.5%, the closed porosity was 1.6%, and the sintering rate was 82.5%, revealing that the bulk density was low and the sintering rate was not high.
Claims
1. a raw material blending step of blending calcium salts and phosphate salts to obtain a mixture having a molar ratio of calcium to phosphorus (Ca / P) of 1.50; a molding step of molding the mixture into a molded body; and a sintering step of sintering the molded body at 1100° C. or more and 1150° C. or less by a reaction sintering method to obtain a sintered body made of β-tricalcium phosphate, A method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial, comprising using hydroxyapatite of a stoichiometric composition as a raw material in the raw material blending step.
2. 2. The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to claim 1, wherein the average primary particle size of the mixture is 0.1 μm or more and 800 μm or less.
3. 2. The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to claim 1, wherein in the molding step, the mixture is molded into a molded body by a direct molding method and a cold isostatic pressing method.
4. The chemical composition of the mixture is composed of phosphoric acid and calcium forming β-tricalcium phosphate, 2. The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to claim 1, wherein in the molding step, the mixture is molded into a molded body without adding a third component which is a sintering aid.
5. forming the mixture into a compact without using hot pressing, hot isostatic pressing or spark plasma sintering in the forming step; 2. The method for producing a dense sintered body of β-tricalcium phosphate for biomaterials according to claim 1, wherein the sintering step is performed without using hot pressing, hot isostatic pressing or spark plasma sintering.
6. 2. The method for producing a dense sintered body of β-tricalcium phosphate for use as a biomaterial according to claim 1, wherein hydroxyapatite of a stoichiometric composition obtained by a reaction sintering method is used as a raw material for the dense sintered body of β-tricalcium phosphate for use as a biomaterial.